Effect of maltodextrin on the oxidative stability of ultrasonically induced soybean oil bodies microcapsules - Li, Zhimin; Sun, Bingyu; Zhu, Ying; Liu, Linlin; Huang, Yuyang; Lu, Mingshou; Zhu, Xiuqing; Gao, Yuan (Frontiers in Nutrition, 2022)
Encapsulation of soybean oil bodies (OBs) using maltodextrin (MD) can improve their stability in different environmental stresses and enhance the transport and storage performance of OBs. In this study, the effects of different MD addition ratios (OBs: MD=1:0, 1:0.5, 1:1, 1:1.5, 1:2 (v/v)) on the physicochemical properties and oxidative stability of freeze-dried soybean OBs microcapsules were investigated. The effect of ultrasonic power (150-250 W) on the encapsulation effect and structural properties of oil body-maltodextrin (OB-MD) microcapsules were studied. The addition of MD to OBs decreased the surface oil content and improved the encapsulation efficiency and oxidative stability of OBs. Scanning electron microscopy images revealed that the sonication promoted the adsorption of MD on the surface of OBs, forming a rugged spherical structure. The oil-body-maltodextrin (OB-MD) microcapsules showed a narrower particle size distribution and a lower -potential absolute value at an MD addition ratio of 1:1.5 and ultrasonic power of 250 W (32.1 mV). At this time, MD-encapsulated OBs particles had the highest encapsulation efficiency of 85.3%. Ultrasonic treatment improved encapsulation efficiency of OBs and increased wettability and the emulsifying properties of MD. The encapsulation of OBs by MD was improved, and its oxidative stability was enhanced by ultrasound treatment, showing a lower hydrogen peroxide value (3.35 meq peroxide/kg) and thiobarbituric acid value (1.65 μmol/kg). This study showed that the encapsulation of soybean OBs by MD improved the stability of OBs microcapsules and decreased the degree of lipid oxidation during storage. Ultrasonic pretreatment further improved the encapsulation efficiency of MD on soybean OBs, and significantly enhanced its physicochemical properties and oxidative stability.